“PRODUKSI DAN PENDAPATAN USAHATANI GETAH KARET (LATEKS) DI DESA BABAYAU KECAMATAN PARINGIN KABUPATEN BALANGAN PROVINSI KALIMANTAN SELATAN” - Yayuk Mintawahyuningsih; Bahrun Bahrun; Ahmad Baparki (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
This research aims to determine the cultivation and cost, income of rubber farmers. The study used a survey method with participatory observation techniques. In its implementation, this activity is for analysis purposes including primary data collection and secondary data. Rubber sap farming income in Babayau Village is currently a fairly serious problem because the income earned by farmers is constantly changing due to various factors, one of which is weather and market conditions.  The sampling technique in this study was the purposive sampling method. Rubber farming activities in Babayau Village, Paringin District, Balangan Regency have technically been running effectively and efficiently from the stages of land clearing, planting, fertilizing, maintaining, and tapping processes. The total production is 73,221 kg for Rp. 7,000, - / kg. The average production is 2,929 / kg perpetual with average revenue of Rp. 20,501,880, per farmer. With an average income of  Rp. 20,501,880 per farmer and an average explicit cost of Rp. 267,675.0 per farmer, the average income is Rp. 20,234,205,04, -per farmer